Konsep Manajemen Jasa Perbankan Syariah dari Perspektif Mazhab Hanafi - Heri Kuncoro Putro; Nurul Inayah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
Islamic Banking Services must be carried out beyond the expectations of the customers served. This is done to increase customer trust in Islamic Banking institutions. Service management aims to improve the quality of service so that customers feel satisfied and have an impact on customer loyalty. The Hanafiyah Mazhab a legal basis for muamalah practices and plays a crucial role in maintaining sustainability and trust in the Islamic banking industry. This article examines the concept and application of Islamic banking service management from the perspective of the Hanafiyah Mazhab. Through a qualitative method approach with descriptive analysis, researchers explore several sources of literature on service management conveyed in the Hanafiyah Mazhab. Data sources from the Al-Quran and Hadith as well as classical books of the Hanafiyah Mazhab. The results of this study state that in the Hanafiyah Mazhab, Islamic banking services must reflect the values ​​of justice, trust and ihsan. Islamic banks need to continue to innovate in presenting services that meet sharia principles by following the development of technological advances in the digital era. The Hanafiyah Mazhab perspective provides a strong legal basis for sharia-based services.